EVALUATION OF SALVIA LANATA LEAF EXTRACT FOR ANTI-INFLAMMATORY AND ANTIOXIDANT ACTIVITY - NOGAI, LIPI; KUMAR, TIRATH; LOHUMI, PANKAJ (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The work is aimed to evaluate the anti-inflammatory and antioxidant activity of the ethanolic leaf extract of Salvia lanata. Methods: Anti-inflammatory activity of the leaf extract of S. lanata at a dose of 100 mg/kg and 200 mg/kg against the standard drug indomethacin at a dose of 10 mg/kg i.p. was evaluated by carrageenan-induced rat paw edema and protein denaturation method. Antioxidant activity was determined by 1, 1 diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging method, reducing power method, and nitric oxide scavenging assay. Results: S. lanata leaf extract showed highly significant dose-dependent efficacy against carrageenan-induced paw edema at a dose of 200 mg/kg and lesser effect at 100 mg/kg. It inhibited heat-induced albumin denaturation with a maximum inhibition of 79.26% at 160 μg/ml. DPPH free radical scavenging activity of extract exhibited inhibition of 25.96%–87.74% within the concentration range of 10 μg/ml–160 μg/ml, nitric oxide assay from 12.26% to 79.22% in the same concentration range. In reducing power assay with an increase in concentrations, an increase in the absorbance of the reaction mixture was observed. Antioxidant activity was compared to standard drug ascorbic acid. Conclusion: The leaf extract of S. lanata has potent anti-inflammatory and antioxidant activity.